Connotative Meaning in Selected Superman Is Dead Song Lyrics - I Kadek Dio Triana; Ni Made Suwari Antari (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The purpose of this analysis is to find out some words that contains with connotative meaning as well as the conveyed message from the song writer on specific object of research in the four superman is dead’s songs based on Jackson (2014) and Hook (1975) theories. The data was taken from the lyrics that was downloaded from the band official site, three of the songs that was analyzed are: “Memories of rose”, “Blackmarket love”, “Goodbye whiskey”, and "Saint of my life" by Superman is Dead in their albums “The Angel and The Outsiders” and "Blackmarket Love". Descriptive qualitative method was implemented as the method in this research. After analyzing the data found from the lyrics, this study found that (1) There are 30 lyrics that contains connotative meaning, (2) Each of the song has different message based on the theme of the song and it was conveyed with different manner by the songwriter.